Evaluasi Kondisi Fisik dan Tingkat Kenyamanan Jalur Pejalan Kaki di Kawasan Pulomas Hasil Proyek Pendukung Infrastruktur Asian Games 2018 - Denny Prasetyo; Agus Dharma Tohjiwa (Syntax Corporation, 2023)
The purpose of this study is to explain the process of building pedestrian paths in Pulomas Area. The type of Research Approach to be used is Quantitative and Qualitative Research because it is most in accordance with the way of data collection and data presentation, namely research used to examine and understand phenomena about what is experienced by research subjects such as behavior, perception and action. From the results of research conducted at the research location there are many trees on the sidewalk, related to the number contained in the number of trees table. Trees placed on the sidewalk, the majority are trees that already existed before the construction of the sidewalk was carried out